Aides stratégiques dans un environnement d'apprentissage en FLE - Anne-Laure Foucher; Maguy Pothier (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Helping to learn, if we place ourselves in a paradigm for teaching and learning within a constructivist perspective, should imply taking into account the learner's knowledge and skills, encouraging the learner to construct his own understanding through real-world experience and helping him promote learning strategies under the teacher's guidance. These are the orientations that we have adopted so as to devise our multimedia learning environment for oral comprehension of FFL with adult learners, by providing didactic interventions which we call "strategic aids" since they aim to induce new learning strategies.In the present paper, we will attempt to show how consistent our didactic choices are, based on a dynamic vision of language learning which focuses on the learning process, individualisation and learner autonomy and concrete achievements we have come up with based upon mediated work phases of our learning environment.